Resveratrol Production in Yeast Hosts: Current Status and Perspectives - Gehad G. Ibrahim; Jinyong Yan; Li Xu; Min Yang; Yunjun Yan (Biomolecules, 2021)
Resveratrol is a plant secondary metabolite known for its therapeutic applications as an antioxidant, anti-cancer, anti-inflammatory, anti-aging, cardio-protective, and neuroprotective agent. Topical formulas of resveratrol are also used for skin disease management and in cosmetic industries. Due to its importance, high resveratrol production is urgently required. Since the last decade, intensive efforts have been devoted to obtaining resveratrol from microorganisms by pathway and metabolic engineering. Yeasts were proven to be excellent host candidates for resveratrol production. In addition to the similar intracellular compartments between yeasts and plants, yeasts exhibit the ability to express genes coding for plant-derived enzymes and to perform post-translational modification. Therefore, this review summarizes the attempts to use yeasts as a platform for resveratrol synthesis as the next promising route in producing high titers of resveratrol from genetically engineered strains.